1989
DOI: 10.1042/bj2640871
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin stimulates inositol trisphosphate-mediated calcium mobilization but not protein kinase C activation in HT29 cells. Involvement of a G-protein

Abstract: It has previously been shown that neurotensin binds to high-affinity receptors in the adenocarcinoma HT29 cell line, and that receptor occupancy leads to inositol phosphate formation. The present study was designed to investigate further the effects of neurotensin on calcium mobilization and protein kinase C (PKC) activation in HT29 cells, and to assess the role of GTP-binding proteins (G-proteins)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 27 publications
6
56
0
Order By: Relevance
“…This effect, generally interpreted as a desensitization of neurotensin receptors, is reported not to occur in HT29 cells (Yamada et al, 1993). Furthermore, in HT29 cells, the G protein involved in phospholipase C activation is insensitive to pertussis toxin (Bozou et al, 1989), whereas in NIE115 cells, the neurotensin effect on inositol phosphate production was reduced by the toxin (Amar et al, 1987 Bozou et al, 1989). Furthermore possibly as a result of differences in coupling mechanisms between the two cell lines, the EC50 for IP1 formation showed one log difference which may explain part of the difference observed in pA2 values.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This effect, generally interpreted as a desensitization of neurotensin receptors, is reported not to occur in HT29 cells (Yamada et al, 1993). Furthermore, in HT29 cells, the G protein involved in phospholipase C activation is insensitive to pertussis toxin (Bozou et al, 1989), whereas in NIE115 cells, the neurotensin effect on inositol phosphate production was reduced by the toxin (Amar et al, 1987 Bozou et al, 1989). Furthermore possibly as a result of differences in coupling mechanisms between the two cell lines, the EC50 for IP1 formation showed one log difference which may explain part of the difference observed in pA2 values.…”
Section: Discussionmentioning
confidence: 95%
“…Cell homogenates from confluent HT29 and NI El 15 cells were prepared as described by Bozou et al (1989). Binding assays were performed at 20'C for 20 min in 50 mM Tris-HCl buffer (pH 7.5) containing 0.2% bovine serum albumin, 1 mM phenanthroline and 1 mM EDTA in the presence of [ the curve.…”
Section: Ligand Binding Assaymentioning
confidence: 99%
“…For instance, the G q/11 -related activation of the phospholipase C pathway could either be followed by an increase in cellular 3', 5'-cyclic guanosine monophosphate (cGMP) through activation of soluble guanylyl cyclase [2,70], or trigger a G s -independent increase in cAMP levels through activation of calcium-dependent adenylyl cyclase [14]. Moreover, if NT stimulated both phospholipase C and protein kinase C in many cells, this peptide only marginally activated the latter branch of this pathway in HT29 cells [12]. Finally, activation of mitogen-activated protein kinases (MAPKs) upon NTS1 stimulation in transfected cells or some tumor cell lines involved either pertussis-sensitive or insensitive G proteins, or both [60].…”
Section: One Pluripotent Receptor Several Cells: How To Combine Econmentioning
confidence: 99%
“…Interactions between NT receptors and G proteins were suggested through pioneering works showing that NT induced inositol phosphate (InsP) production [1,22,70], inhibited cAMP formation [10], and that the "high affinity NT binding site" was sensitive to guanine nucleotides [12]. Molecular studies thereafter indicated that most of these effects were attributable to NTS1.…”
Section: Introductionmentioning
confidence: 99%
“…It causes inositol 1,4,5-trisphosphate (InsP 3 ) production and increase in the cytosolic calcium concentration ([Ca 2+ ] i ) through the activation of phospholipase C (PLC) (Goedert et al, 1984;Bozou et al, 1989;Hermans et al, 1992). In another signalling pathway, neurotensin modulates the intracellular cyclic nucleotide level including cyclic GMP (Gilbert & Richelson, 1984;Amar et al, 1985) and cyclic AMP (Bozou et al, 1986;Yamada et al, 1994).…”
Section: Introductionmentioning
confidence: 99%